Polymeric compositions of medical devices account for the variations in Candida albicans biofilm structural morphology - Sumalapao, Derick Erl P. (Animo Repository, 2020)
The increase in the number of fungal infections has been associated with the prevalent use of medical devices. This study assessed the morphological structure of Candida albicans biofilms on the surfaces of medical devices using scanning electron microscopy and characterized the polymeric compositions of these medical devices using infrared spectroscopic study. Biofilms on the surfaces of these medical devices exhibited variations in morphological topographies ranging from the presence of ellipsoid and spherical yeast cells joining end to end, to the growth of pseudohyphae and hyphae formation with chains of cylindrical cells, and the formation of several microcolonies entrenched in a polymeric matrix. The differences in the spectroscopic profiles of the medical devices accounted for the variations in the structural morphology of these biofilms. Spectral studies on polyvinyl chloride endotracheal tube revealed sp3-CH stretching frequencies at 2959, 2926, and 2858 cm-1 with CCl stretching frequencies at 636 cm-1 and 693 cm-1. Silicone polymer containing medical devices had SiOSi and SiC stretching frequencies identified at 1096 cm-1 and 804 cm-1 for the silicone urinary catheter, while the stretching frequencies were identified at 1005 cm-1 and 862 cm-1 for the silicone nasogastric tube, respectively. Given the information on the variations in the morphological appearance of the biofilms on medical device surfaces, these differences on the polymeric compositions of the medical devices can provide explanations on the adhesion potential, biofilm formation, structural morphology, and subsequent susceptibility pattern of the sessile organism to antifungal drugs. © 2020 Beijing Academy of Agriculture and Forestry Sciences, Institute of Plant and Environment Protection.